Homesteading : a backyard guide to growing your own food, canning, keeping chickens, generating your own energy, crafting, herbal medicine, and more - Gehring, Abigail R. (Skyhorse Publishing, 2014)
Wherever you live - farm, suburb, or even city - The Homesteading Handbook will show you how to embrace a more self-sufficient lifestyle. Learn to plan, plant, and harvest your own organic garden. Enjoy fruits and vegetables year-round by canning, drying, and freezing. Build and install alternate energy devices such as solar panels or geothermal heat pumps. Who doesn't want to shrink their carbon footprint, save money, and eat fresh, homegrown food whenever possible? Even readers who are very much on the grid will embrace this fully-illustrated guide on the basics of living the good, clean life. From beekeeping to basket weaving to baking, this handy guide has everything you need to experience the satisfaction that comes with self-sufficiency, as well as the assurance that you have done your part to help keep our planet green.--COVER.